GOVERNMENT EFFORTS TO IMPLEMENT THE GREEN BUILDINGS MARKET IN DKI JAKARTA - Hendi Prihanto (Universitas prof. Dr. Moestopo (Beragama), 2021)
Green buildings are very important and become a necessity that is environmentally friendly, this research was conducted to analyze the government's efforts to implement the market with buildings through aspects that influence it such as intellectual capital (human capital, organizational capital, customer capital) and governance. Sampling was carried out randomly through the distribution of questionnaires carried out in a number of markets spread across the DKI Jakarta area as a population, so that the results of research observations obtained a number of 170 samples filled in by market managers from different regions. Multiple linear regression and statistical hypothesis testing t are analyzes used to test hypotheses with data analysis tools using SPSS software. The research concludes that the dimensions of intellectual capital, namely human capital and organizational capital, have a significant positive effect, while customer capital and governance do not have a significant effect on market implementation with green buildings. The limitation of the study is that the sample used at random has not been able to conclude the overall results, In addition, the questionnaire submitted has the potential to be inconsistent with existing facts because of the possibility of subjectivity that can occur.